Bicarbonate, carbon dioxide and pH sensing via mammalian bicarbonate-regulated soluble adenylyl cyclase - Rossetti, Tom (Interface Focus, 2021)
Soluble adenylyl cyclase (sAC; ADCY10) is a bicarbonate (HCO(3)(−))-regulated enzyme responsible for the generation of cyclic adenosine monophosphate (cAMP). sAC is distributed throughout the cell and within organelles and, as such, plays a role in numerous cellular signalling pathways. Carbonic anhydrases (CAs) nearly instantaneously equilibrate HCO(3)(−), protons and carbon dioxide (CO(2)); because of the ubiquitous presence of CAs within cells, HCO(3)(−)-regulated sAC can respond to changes in any of these factors. Thus, sAC can function as a physiological HCO(3)(−)/CO(2)/pH sensor. Here, we outline examples where we have shown that sAC responds to changes in HCO(3)(−), CO(2) or pH to regulate diverse physiological functions.